God Exists, God Speaks and God Works Based on Hebrews 1-4 - Feri Dolf Djami Hae; Janes Sinaga; Juita Lusiana Sinambela (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The aims of this study are: The Letter to the Hebrews affirms that God exists, God speaks, and God works to save everyone, especially for the needs of the faith growth of Jewish Christians in knowing Jesus Christ. Stating the purpose of the letter to the Hebrews to fully awaken the reader to the revelation of God's salvation through Jesus as Lord and Savior in 7 phrases from Hebrews 1-4. This study uses a qualitative method of literature study. In the book of Hebrews 1-4 reveals that God exists, God speaks and God works. The Epistle to the Hebrews explains to Hebrew Christians the true meaning of priesthood work and sacrificial rites in Old Testament times as foreshadowing and foreshadowing the work of Christ as the Lamb of God and our Mediator in the plan of salvation. The death of Jesus on the cross is the culmination of the revelation of God's character. Which suggests two very different things: the unfathomable evil of man and, God's unfailing love.